2020
DOI: 10.1124/mol.119.117721
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin Reduces Activity of Cardiac Ryanodine Receptor 2; A Potential Mechanism for Its Cardioprotective Action

Abstract: Phenytoin is a hydantoin derivative that is used clinically for the treatment of epilepsy and has been reported to have antiarrhythmic actions on the heart. In a failing heart, the elevated diastolic Ca 21 leak from the sarcoplasmic reticulum can be normalized by the cardiac ryanodine receptor 2 (RyR2) inhibitor, dantrolene, without inhibiting Ca 21 release during systole or affecting Ca 21 release in normal healthy hearts. Unfortunately, dantrolene is hepatotoxic and unsuitable for chronic long-term administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…Some drugs have already been shown to reduce diastolic RyR2 Ca 2+ leak. Notably, dantrolene reduces diastolic Ca 2+ leak in failing canine, 123 rabbit, 124 and human heart 125 but not corresponding species (canine, rabbit, and human) nonfailing heart. 124,125 125 It is important that therapies do not depress systolic function, especially in the compromised failing heart.…”
Section: ■ Combining the Modelsmentioning
confidence: 94%
See 2 more Smart Citations
“…Some drugs have already been shown to reduce diastolic RyR2 Ca 2+ leak. Notably, dantrolene reduces diastolic Ca 2+ leak in failing canine, 123 rabbit, 124 and human heart 125 but not corresponding species (canine, rabbit, and human) nonfailing heart. 124,125 125 It is important that therapies do not depress systolic function, especially in the compromised failing heart.…”
Section: ■ Combining the Modelsmentioning
confidence: 94%
“…Notably, dantrolene reduces diastolic Ca 2+ leak in failing canine, 123 rabbit, 124 and human heart 125 but not corresponding species (canine, rabbit, and human) nonfailing heart. 124,125 125 It is important that therapies do not depress systolic function, especially in the compromised failing heart. Interestingly, phenytoin and dantrolene do not compete for the same binding site on RyR2.…”
Section: ■ Combining the Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite this, the 'SHO-IN' clinical trial seeks to determine the safety and efficacy of dantrolene on patients with chronic HF [Japanese Registry of Clinical Trials identifier 61180059] (Kobayashi et al, 2020). Recent work has shown that phenytoin, a member of the same class of hydantoin compounds, shares the same RyR2 inhibitory effects as dantrolene (Ashna et al, 2020). In vitro application of phenytoin to RyR2 channels isolated from failing human hearts shows that phenytoin reversibly inhibits RyR2 which subsequently inhibits diastolic cytoplasmic, but not systolic, Ca 2+ release (Ashna et al, 2020).…”
Section: Ryr2mentioning
confidence: 99%
“…Recent work has shown that phenytoin, a member of the same class of hydantoin compounds, shares the same RyR2 inhibitory effects as dantrolene (Ashna et al, 2020). In vitro application of phenytoin to RyR2 channels isolated from failing human hearts shows that phenytoin reversibly inhibits RyR2 which subsequently inhibits diastolic cytoplasmic, but not systolic, Ca 2+ release (Ashna et al, 2020). Interestingly, phenytoin is currently used clinically as a Na + channel blocker to treat epilepsy, therefore there is scope to determine the potential therapeutic use of phenytoin in HF (Figure 4).…”
Section: Ryr2mentioning
confidence: 99%